3D Bioprinting: 3D Bioprinting Using a Templated Porous Bioink (Adv. Healthcare Mater. 14/2016). Issue 14 (20th July 2016) - Armstrong, James P. K.; Burke, Madeline; Carter, Benjamin M.; Davis, Sean A.; Perriman, Adam W.
Abstract : A.W. Perriman and co‐workers describe a new cell‐containing hybrid bio‐ink that allows the 3D printing of physiological architectures with templated micropores on page 1724. The printed constructs are then used in cartilage and bone tissue engineering, giving rise to well‐distributed extracellular matrix components.